Discursive Legitimation of Public Security Militarization in Nayib Bukele´s Government in El Salvador - Cristancho Cuesta, Andrea (2021)
The legitimation of Armed Forces as the predominant actor for public security tasks has been constant in the government discourse of Salvadoran President Nayib Bukele since the beginning of his administration in June 2019. This research analyzes the rituals and ceremonies of the celebration of 198 anniversary of Salvadoran independence, time at which the Salvadoran president displays the centrality of his figure, shows his support through phrases, images, metaphors, tweets, and retweets that frame all the virtues of the military institution and define and justify the public security policy of its administration.